Self-control, Victimization, and their Influence on Risky Lifestyles: A Longitudinal Analysis Using Panel Data - Schreck, Christopher J. (Journal of quantitative criminology, 2006)
This research expands past investigations into the influence of low self-control as a risk factor for criminal victimization. Specifically, we consider two questions: (1) whether low self-control at one point in time can predict future victimization, and (2) whether victims alter lifestyle choices (like their own delinquency and contact with delinquent peers) in response to their earlier victimization. We answered these questions using three waves of adolescent panel data from the evaluation of the Gang Resistance Education and Training program. Our results support the predictions of self-control theory, showing that low self-control measured at an earlier time is associated with later victimization, even after controlling for past victimization, delinquency, social bonds, and delinquent peer contact. Likewise, self-control appears to influence the relationship between earlier victimization and later lifestyles.